(NkNIGA )QÆ ^AS (B/s)E - (N{PAKOW(B, (Na(B.,s ((NkI)QÇW (B:s)E (NdN)QÆPRO(B,s)E, 1977)
(Nu KNIZ)QÆ ZROBLENO KOROTKIJ OGLQD WIDAWNI^OÇ SPRAWI NA uKRAÇNÆ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NwIDAWNI^A SPRAWAs; (NKNIGAs; (NWIDAWNI^A SPRAWAs; (N[RIFTs; (NGRAF)QÆKAs)E; (NPOL)QÆGRAFÆQs)E; (NL)QÆNOGRAW@RAs)E; (NMAKETUWANNQs; (NKSILOGRAF)QÆQs)E